Palaeogeographical reconstruction and hydrology of glacial Lake Purcell during MIS 2 and its potential impact on the Channeled Scabland, USA. (31st January 2020) - Peters, Jared L.; Brennand, Tracy A.
Abstract : Large, ice‐marginal lakes that were impounded by the maximally extended Cordilleran Ice Sheet (CIS) provided source waters for the extraordinarily large floods that formed the Channeled Scabland of Washington and Idaho, USA. However, flood flows that drained CIS meltwater and contributed to landscape evolution during later stages of deglaciation have hitherto been poorly investigated. This paper provides the first evidence for such a late deglacial floodwater source: glacial Lake Purcell (gLP). Sedimentary evidence records the northward extension of gLP from Idaho, USA into British Columbia, Canada and establishes its minimum palaeogeographical extent. Sedimentary evidence suggests that the deglacial Purcell Lobe was a capable ice dam that impounded large volumes of gLP water. A review of glacio‐isostatically affected lakes during CIS deglaciation suggests that gLP could have been subjected to tilts ranging from 0 to >1.25 m km −1 . Sedimentary evidence suggests high lake plane tilts (⪆1.25 m km −1 ) are the most likely to have affected gLP. Using this, the palaeogeography and volume of gLP are modelled, revealing that ~116 km 3 of water was susceptible to sudden drainage into the Channeled Scabland via the Columbia River system. This calculation is supported by sedimentary and geomorphic evidence compatible with energetic flood flows along the gLP drainage route and suggests gLP drained suddenly, causing significant landscape change.